Gut Microbiota-Immune System Crosstalk and Pancreatic Disorders - D. Pagliari; A. Saviano; E. E. Newton; M. L. Serricchio; A. A. Dal Lago; A. Gasbarrini; R. Cianci (Mediators of Inflammation)
Gut microbiota is key to the development and modulation of the mucosal immune system. It plays a central role in several physiological functions, in the modulation of inflammatory signaling and in the protection against infections. In healthy states, there is a perfect balance between commensal and pathogens, and microbiota and the immune system interact to maintain gut homeostasis. The alteration of such balance, called dysbiosis, determines an intestinal bacterial overgrowth which leads to the disruption of the intestinal barrier with systemic translocation of pathogens. The pancreas does not possess its own microbiota, and it is believed that inflammatory and neoplastic processes affecting the gland may be linked to intestinal dysbiosis. Increasing research evidence testifies a correlation between intestinal dysbiosis and various pancreatic disorders, but it remains unclear whether dysbiosis is the cause or an effect. The analysis of specific alterations in the microbiome profile may permit to develop novel tools for the early detection of several pancreatic disorders, utilizing samples, such as blood, saliva, and stools. Future studies will have to elucidate the mechanisms by which gut microbiota is modulated and how it tunes the immune system, in order to be able to develop innovative treatment strategies for pancreatic disorders.